2014
DOI: 10.1128/aac.02000-13
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of PD 404,182 as an Anti-HIV and Anti-Herpes Simplex Virus Microbicide

Abstract: ؉ T cells, macrophages, and dendritic cells (CC 50 , >300 M). PD also exhibited high stability in pH-adjusted Dulbecco's phosphate-buffered saline with little to no activity loss after 8 weeks at pH 4 and 42°C, indicating suitability for formulation for transportation and storage in developing countries. Finally, for the first time, we show that PD inactivates herpes simplex virus 1 (HSV-1) and HSV-2 at submicromolar concentrations. Due to the prevalence of HSV infection, the ability of PD to inactivate HSV ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 80 publications
0
9
0
Order By: Relevance
“…This is an antibiotic against Gram-negative bacteria that is known to inhibit 3-deoxy- d -manno-octulosonic acid 8-phosphate synthase [ 19 ]. PD 404,182 has also previously been shown to be a highly potent inhibitor of HCV and HIV by causing physical disruption of the virion [ 20 , 21 ], and its ease of synthesis suggests it is tractable for use as an antiviral [ 22 ]. It has additionally been identified as an irreversible inhibitor of dimethylarginine dimethylaminohydrolase 1 and histone deacetylase 8 via irreversible binding to cysteine residues [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is an antibiotic against Gram-negative bacteria that is known to inhibit 3-deoxy- d -manno-octulosonic acid 8-phosphate synthase [ 19 ]. PD 404,182 has also previously been shown to be a highly potent inhibitor of HCV and HIV by causing physical disruption of the virion [ 20 , 21 ], and its ease of synthesis suggests it is tractable for use as an antiviral [ 22 ]. It has additionally been identified as an irreversible inhibitor of dimethylarginine dimethylaminohydrolase 1 and histone deacetylase 8 via irreversible binding to cysteine residues [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…6 H -6-Imino-(2,3,4,5-tetrahydropyrimido)[1,2- c ]-[1,3]benzothiazine (PD 404182, 79 ), is a commercially available heterocyclic pyrimidobenzothiazine and a suitable lead compound for SAR studies due to its simple synthetic methodology [168]. PD 404182 ( 79 ) is a compound listed in the Library of Pharmacologically Active Compounds (LOPAC) and is reported to have antibacterial [168,169] and antiviral [170,171] activity. Ghebremariam et al [61] utilized a colorimetric assay to screen a library of over 1200 compounds for their ability to inhibit the conversion of ADMA to l -citrulline and dimethylamine by recombinant human DDAH-1.…”
Section: Pharmacological Inhibition Of Ddahmentioning
confidence: 99%
“…(1, PD 404182) 11-14 as a new antiviral agent against human hepatitis C virus (HCV), 15,16 HIV, [16][17][18][19][20] simian immunodeficiency virus (SIV), 16 and herpes simplex virus (HSV) (Figure 1). 20 A structureattachment and membrane fusion to host cells as exemplified by DS 5000 (adsorption inhibitor) 21 and enfuvirtide (fusion inhibitor) 6 .…”
Section: Introductionmentioning
confidence: 99%
“…20 A structureattachment and membrane fusion to host cells as exemplified by DS 5000 (adsorption inhibitor) 21 and enfuvirtide (fusion inhibitor) 6 . Although it was suggested that compound 1 exerts its virucidal effect against viral particles, 20 its antiviral mechanism of action has not yet been sufficiently detailed.…”
Section: Introductionmentioning
confidence: 99%